Theranostic Strategy of Focused Ultrasound Induced Blood-Brain Barrier Opening for CNS Disease Treatment - Chen, Ko-Ting; Wei, Kuo-Chen; Liu, Hao-Li (Frontiers in Pharmacology, 2019)
Focused Ultrasound (FUS) in combination with gaseous microbubbles has emerged as a potential new means of effective drug delivery to the brain. Recent research has shown that, under burst-type energy exposure with the presence of microbubbles, this modality can transiently permeate the blood-brain barrier (BBB). The bioavailability of therapeutic agents is site-specifically augmented only in the zone where the FUS energy is targeted. The non-invasiveness of this approach makes FUS-induced BBB opening a novel and attractive means to perform localized CNS therapeutic agent delivery. Over the past decade, FUS-BBB opening has been preclinically confirmed to successfully enhance CNS penetration of therapeutic agents including chemotherapeutic agents, therapeutic peptides, monoclonal antibodies, and nanoparticles. Recently, a number of clinical human trials have begun to explore clinical utility. This review article, explores this technology through its physical mechanisms, summarizes the existing preclinical findings (including current medical device designs and technical approaches), and summarizes current ongoing clinical trials.